2021
DOI: 10.3390/biology10050397
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 16S rRNA Gene-Based Phylogenetic Diversity of Archaeal Communities in Halite-Crystal Salts Processed from Natural Saharan Saline Systems of Southern Tunisia

Abstract: A thorough assessment of the phylogenetic diversity and community structure of halophilic archaea from three halite-crystal salts, processed from two separated saline systems of Southern Tunisia has been performed using culture dependent and independent methods targeting different regions of 16S rRNA gene sequences including DGGE, 16S rRNA clone libraries and Illumina Miseq sequencing. Two samples, CDR (red halite-crystal salts) and CDW (white halite-crystal salts), were collected from Chott-Eljerid and one sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Genome‐based functional analyses of microbes within the cryopeg brine of a 40 000‐year‐old permafrost identified Marinobacter as a dominant taxon within the community (Rapp et al ., 2021). Both studies of laboratory‐synthesized brine inclusions and those that focus on in situ ecology have revealed the complexity and dynamics of halophile communities that subsist or survive in these habitats (Colangelo‐Lillis et al ., 2016; Huby et al ., 2021; Najjari et al ., 2021; Rapp et al ., 2021). Other studies have focused on organic compounds within inclusions of halite (Chan et al ., 2018) (and billions‐of‐years‐old fluid inclusions of quartz—mineralized silicon dioxide— Schreiber et al ., 2017, and baryte—mineralized barium sulfate—Mißbach et al ., 2021).…”
Section: Aqueous Brines Conserve Cell Viabilitymentioning
confidence: 99%
“…Genome‐based functional analyses of microbes within the cryopeg brine of a 40 000‐year‐old permafrost identified Marinobacter as a dominant taxon within the community (Rapp et al ., 2021). Both studies of laboratory‐synthesized brine inclusions and those that focus on in situ ecology have revealed the complexity and dynamics of halophile communities that subsist or survive in these habitats (Colangelo‐Lillis et al ., 2016; Huby et al ., 2021; Najjari et al ., 2021; Rapp et al ., 2021). Other studies have focused on organic compounds within inclusions of halite (Chan et al ., 2018) (and billions‐of‐years‐old fluid inclusions of quartz—mineralized silicon dioxide— Schreiber et al ., 2017, and baryte—mineralized barium sulfate—Mißbach et al ., 2021).…”
Section: Aqueous Brines Conserve Cell Viabilitymentioning
confidence: 99%
“…For example, an almost linear correlation was observed in 143 microbial genera, where the rRNA G+C content gradually increased from about 45% G+C in psychrophilic bacteria to about 55% G+C in thermophilic bacteria 15 . But at least 22 other studied genera showed temperatureindependent variations because the rRNA G+C content was found to be influenced by other factors, including high-salt conditions and host-restricted lifestyles 15,[24][25][26][27][28][29] . Collectively, these studies showed that using the content of rRNA genes as a molecular thermometer is a promising approach but on its own it lacks accuracy, raising the question: Do ribosomal genes contain other markers of thermal adaptation that could help estimate the optimal growth conditions for a given organism?…”
Section: Introductionmentioning
confidence: 98%
“…Extremely halophilic archaea (Class Halobacteria) thrive in arid and semi-arid saline and hypersaline environments, such as solar salterns, hypersaline marshes and saline ponds (Viver et al 2021(Viver et al , 2019. They have also been isolated from low and fluctuating salinity environments (Dombrowski et al 2019;Najjari et al 2021;Purdy et al 2004;Zhang et al 2021). Organisms thriving in such ecosystems are exposed to salinity fluctuations (Mani et al 2020;Viver et al 2021;Youssef et al 2014), extreme dryness (Bolhuis et al 2006;Merino et al 2019), fluctuating temperatures (Shukla et al 2016), intense solar radiation (UV) (DasSarma & DasSarma 2018;Jones & Baxter 2017;Jones et al 2018;Yamagishi et al 2018), as well as nutritional deficiency (Robinson et al 2015;Stan-Lotter et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tunisia harbors several endorheic saline lake ecosystems Sebkhas and Chotts characterized by unstable climatic conditions, due to the periodic flooding by the subsurface ground water associated with high salt conditions during dry phases. Those located in arid and semi-arid regions constituted an important habitat in terms of biodiversity (El Hidri et al 2013;Guesmi et al 2013;Najjari et al 2021;Neifar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation